Sirtuin 1 genetic variation, energy balance and colorectal cancer risk by sex and subsite in the Netherlands Cohort Study. Issue 1 (December 2018) - Simons, C.; Schouten, L.; Godschalk, R.; Schooten, F.; Brandt, P.; Weijenberg, M.
Abstract Sirtuin 1 (SIRT1) is an energy-sensing protein, which may affect tumorigenesis. We usedSIRT1 variants as time-independent indicators of SIRT1 involvement in carcinogenesis and we studied two taggingSIRT1 variants in relation to colorectal cancer (CRC) risk. We also evaluated known energy balance-related CRC risk factors withinSIRT1 genotype strata. The Netherlands Cohort Study includes 120, 852 individuals and has 20.3 years follow-up (case-cohort: nsubcohort  = 5000; nCRC cases  = 4667). At baseline, participants self-reported weight, weight at age 20, height, trouser/skirt size reflecting waist circumference, physical activity, and early life energy restriction.SIRT1 rs12778366 and rs10997870 were genotyped in toenail DNA available for ~75% of the cohort. Sex- and subsite-specific Cox hazard ratios (HRs) showed that the rs12778366 CC versus TT genotype decreased CRC and colon cancer risks in women (HRCRC  = 0.53, 95% confidence interval: 0.30–0.94) but not men. Multiplicative interactions were observed betweenSIRT1 variants and energy balance-related factors in relation to CRC endpoints, but the direction of associations was not always conform expectation nor specific to one genotype stratum. In conclusion, these results support SIRT1 involvement in colon cancer development in women. No conclusions could be made regarding a modifying effect ofSIRT1 variants on associations between energy balance-related factors and CRC risk.